Remote programming for heterogeneous sensor networks - Bhatia, Vishal (Kansas State University, 2008)
Deluge is a protocol used for remote re-programming of nodes in a wireless sensor networks by injecting messages into a network of motes without having the motes directly connected to the PC. It uses the 3-way handshake protocol consisting of 3 types of messages: advertise, request and data. The protocol is very useful but is restricted to homogeneous networks wherein all nodes must be programmed with the same code. This project is an attempt to modify the existing protocol to work for heterogeneous networks where different motes function differently and have to be programmed differently. The project was developed using Java and nesC (a dialect of C) which supports component based programming. The nodes run an operating system called tinyOS which is specifically designed for sensor networks. The system was tested on a network of micaZ and TelosB motes.
Keywords: Deluge; Heterogeneous; Engineering, General (0537); Information Science (0723)